Ketidaklangsungan Ekspresi dalam JuduI Cerita Rubrik “Nah ini Dia” Harian Pos Kota - Andi Hallang Lewa; Budi Santoso (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2020)
Indirrect expression is widely used in writing news on the mass media, including short stories in newspapers. This paper tries to describe indirrect expressions in the title of the storiy on Poskota daily’s Column "Nah Ini Dia". Data is taken from the title of the storiy on Poskota daily’s Column "Nah Ini Dia", 2020, March-April edition. The research method uses descriptive qualitative methods. Documentation techniques used in collecting data. Data analysis used Riffatere's indirrect expressions theory with focused on analysing displacing of meaning, distorcing of meaning, and creating of meaning. The results show that indirrect expression is occur due to displacing of meaning, distorcing of meaning, and creating of meaning. Displacing of meaning appear in the form of figurative language such as metaphor, personification, periphrasis, and euphemism. distorcing of meaning appears in the form of ambiguity, contradiction, and irony.  Creatiing of meaning appears in the form of simitri and two types of rhythm: assonance and consonance. Using indirect expressions make the title of the story  more polite and have poetic sense.